2002
DOI: 10.1074/jbc.m108938200
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine Myotoxicity Is Mediated by Mitochondria

Abstract: We have investigated the effects of the myotoxic local anesthetic bupivacaine on rat skeletal muscle mitochondria and isolated myofibers from flexor digitorum brevis, extensor digitorum longus, soleus, and from the proximal, striated portion of the esophagus. In isolated mitochondria, bupivacaine caused a concentration-dependent mitochondrial depolarization and pyridine nucleotide oxidation, which were matched by an increased oxygen consumption at bupivacaine concentrations of 1.5 mM or less at pH 7.4, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 57 publications
5
114
1
2
Order By: Relevance
“…In rat hippocampal slices, application of millimolar concentrations of lidocaine, but not bupivacaine, resulted in elevated expression of cleaved caspase 3, the primary executioner of apoptosis [38] . Active oxidative metabolism involving mitochondrial dysfunction and alterations of Ca 2+ homeostasis has been also suggested in bupivacaine-induced myotoxicity [36] . These findings raise an interesting possibility that some, if not all, of these pathways could modulate specific LA-induced myotoxicity independently or collaboratively.…”
Section: Wwwnaturecom/aps Maurice Jm Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In rat hippocampal slices, application of millimolar concentrations of lidocaine, but not bupivacaine, resulted in elevated expression of cleaved caspase 3, the primary executioner of apoptosis [38] . Active oxidative metabolism involving mitochondrial dysfunction and alterations of Ca 2+ homeostasis has been also suggested in bupivacaine-induced myotoxicity [36] . These findings raise an interesting possibility that some, if not all, of these pathways could modulate specific LA-induced myotoxicity independently or collaboratively.…”
Section: Wwwnaturecom/aps Maurice Jm Et Almentioning
confidence: 99%
“…Studies on both acute and longterm myotoxic effects of LAs after continuous peripheral nerve blocks in a clinically relevant setting reaffirmed bupivacaine's exceptional rate of myotoxicity [6,7] . Excessively increased intracellular [Ca 2+ ] level due to an alteration of Ca 2+ homeostasis has been suggested as a cause of bupivacaine-induced muscle cell death [35] , perhaps mediated by mitochondria [36] . However, detailed molecular mechanisms, especially the signaling pathways, by which the LAs exert their cytotoxicities remain to be explored.…”
Section: Wwwnaturecom/aps Maurice Jm Et Almentioning
confidence: 99%
“…A small number of studies have attempted to establish the mechanisms by which LAs induce chondrotoxicity. It has been shown that LAs may cause mitochondrial dysfunction, inhibition of voltage-gated Na + and Ca 2+ channels, or potassium channel blockade [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, mitochondrial dysfunction results in ATP depletion 47 and in turn is expected to have a major impact on intracellular Ca 2+ homeostasis 48 . In addition, active oxidative metabolism is a key determinant in bupivacaine toxicity, and bupivacaine myotoxicity is a relevant model of mitochondrial dysfunction involving the permeability transition pore (PTP), a cyclosporin A-sensitive inner membrane channel that plays a key role in many forms of cell death, and Ca 2+ dysregulation, and that it represents a promising system to test new PTP inhibitors that may prove relevant in spontaneous myopathies where mitochondria have long been suspected to play a role 49 . Longacting local anesthetics induce marked negative inotropic and lusitropic effects on cardiomyocytes and such effect was mainly because of the impairment of calcium handling 50 .…”
Section: Local Anesthetics and Mitochondrionmentioning
confidence: 99%